2019
DOI: 10.1039/c9fo00318e
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotection of auraptene from the peels of citrus fruits against 17α-ethinylestradiol-induced cholestasis in mice by activating farnesoid X receptor

Abstract: Auraptene protects against estrogen-induced cholestasis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Studies have shown that FXR could inhibit the bile acid synthase CYP7A1 and CYP8B1, promote the expression of bile acid e ux transporter, reduce the expression of bile acid uptake transporter [22][23][24]. In this study, the way of OCA improving cholestasis was mainly based on increasing bile acid e ux transporter to promote bile excretion.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have shown that FXR could inhibit the bile acid synthase CYP7A1 and CYP8B1, promote the expression of bile acid e ux transporter, reduce the expression of bile acid uptake transporter [22][23][24]. In this study, the way of OCA improving cholestasis was mainly based on increasing bile acid e ux transporter to promote bile excretion.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have found that estrogens can increase the activity CYP7A1, CYP8B1 and CYP27A1, along with small transient increases in BA production ( Davis et al, 1986 ; Chico et al, 1996 ; Yang et al, 2020 ). In addition, estrogens can inhibit the expression of BA metabolic enzymes, especially phase II enzymes (such as hydroxysteroid sulfotransferase 2a1, Sult2a1), which in turn decreases the metabolism of bile acids, leading to an increased levels of unconjugated and hydrophobic bile acids in hepatocyte, and a decrease in bile flow ( Zamek-Gliszczynski et al, 2006 ; Zollner and Trauner, 2006 ; Wang et al, 2019 ).…”
Section: Pathophysiological Mechanisms Of Eicmentioning
confidence: 99%
“…As one of the most important BA sensors in maintaining BA homeostasis, nuclear receptor, farnasol X receptor (FXR) regulates the levels of hepatic transporters to affect BA homeostasis. Estrogens and their metabolites can inhibit the expression of FXR, which decreases the expression of BA transporters in the canalicular membranes of the liver ( Wang et al, 2019 ). This can cause retention of bile acids in hepatocytes and alters the compositions of BA, which subsequently leads to cholestatic liver injury ( Lee et al, 2000 ; Stieger et al, 2000 ).…”
Section: Pathophysiological Mechanisms Of Eicmentioning
confidence: 99%
“…Also the interaction of auraptene and the farnesoid X receptor, first put in evidence Epifano et al (2012), was further characterized studying the hepatoprotective action by auraptene against 17a-ethinylestradiol (EE)-induced cholestasis both in vitro using mice primary hepatocytes and in vivo in C57BL/6 mice (Wang et al 2019). These Authors first determined that compound (2) can modulate FXR target genes involved in the bile acid transport and synthesis.…”
Section: Auraptenementioning
confidence: 99%